Taxpayer Awareness And Understanding Of Tax Regulations On Taxpayer Compliance With Tax Sanctions As A moderating - Putri Dwi Puji Lestari; Syafira Surya Lestianti (Yayasan Az Zukhruf Cendikia, 2024)
Purpose – this research aims to provide empirical evidence regarding the influence of Taxpayer Awareness and Understanding Of Tax Regulations On Taxpayer Compliance, with Tax Sanctions As A Moderating Variable. Design/methodology/approach – This research adopts a quantitative approach. The study was conducted using questionnaires distributed to individuals with a Taxpayer Identification Number (NPWP), including those who earn income from employment in companies or from their own business ventures. A total of 51 questionnaires were distributed via social media, with each questionnaire containing 33 statements for respondents to answer. The distribution of the questionnaire yielded responses from 51 individuals from a single region. To analyze the data, the researchers used PLS-SEM version 3.0. Findings – The results of this research indicate that Taxpayer Awareness has a positive and significant effect On Taxpayer Compliance, and Understanding Tax Regulations also has a positive and significant effect On Taxpayer Compliance. However, Tax Sanctions were found not to strengthen the relationship between Taxpayer Awareness and Taxpayer Compliance, nor did Tax Sanctions strengthen the relationship between Understanding Tax Regulations and Taxpayer Compliance. Research limitations/implications – This study focuses On Taxpayer Compliance, and it is an intriguing research topic that discusses Taxpayers Awareness and Understanding of Tax Regulations, which are based on attitudes and the integrity and responsibility traits. The study emphasizes the importance of enhancing Taxpayers Awareness and Understanding of Tax Regulations to improve compliance rates, which can assist policymakers in designing an effective tax framework. Furthermore, it highlights the progress of a country driven by increased awareness and understanding, as these are obligations that every individual with such responsibilities must fulfill